George Eliot and Italy - Thompson, A. author. aut Link
X, 243 p.
Keywords: This study considers George Eliot's novels in relation to Dante and to nineteenth-century Italian culture during the Italian national revival and shows how these helped shape her fiction. Thompson argues that Eliot was able to draw selectively on a powerful Risorgimento mythology of national regeneration and that her engagement with the work of Dante Alighieri increases steadily in her later novels, where the Divine Comedy becomes a sustaining metaphor for Eliot's meliorist vision and for her theme of moral growth through suffering.